Morphometric characterization of Eryngium viviparum (Umbelliferae): description of a new subspecies from the Iberian Peninsula - Romero Bujan, Maria Inmaculada; Real, Carlos (Phytotaxa, 2014)
Eryngium viviparum is an endemic plant of the Atlantic regions of Europe. Surveys carried out in recent years in the wetlands of northwest Spain have led to the identification of several previously undetected subpopulations of this species in inland areas with markedly Mediterranean bioclimatic characteristics that constitute the southern limit of this species. However, these populations overlap with the distribution of the Iberian endemic E. galioides, similar in size and morphology. We developed a biometric study on herbarium vouchers that has enabled us to identify a new subspecies, subspecies bariegoi, distributed in a limited geographical zone in Mediterranean areas of the northwest Iberian Peninsula.